The Effect of Seaweed (Eucheuma spinosum) Fortification on The Quality of Pekdos - Marwah Iwada; Sumarto Sumarto; Dewita Dewita (Berkala Perikanan Terubuk, 2021)
This study aims to determine the effect of fortification of seaweed (Eucheuma spinosum)on the quality of pekdos and determine the amount of seaweed addition to producing thebest quality of pekdos. The research method used was experimental with the processingof pekdos with the addition of seaweed porridge (E. spinosum) in differentconcentrations. The research design was a completely randomized design (CRD)consisting of 4 treatment levels, P0 (0%), P1 (5%), P2 (10%), and P3 (15%). Parameteranalysis of organoleptic, moisture content, ash, protein, fat, and crude fiber. The resultsshowed that seaweed fortification had a significant effect on the 95% confidence levelon the quality of pekdos. The addition of 10% (P2) seaweed produced the best qualitypekdos. The pekdos has a neat appearance intact, slightly hollow, attractive, and slightlyyellowish-white; the aroma is not fishy, fresh, fragrant, and specific type of pekdosmackerel; tasted specific type of pekdos taste, savory, and very tasty; and a chewy soft,and easy-to-bite texture; pekdos has 37.40% moisture; 3.54% ash; 14.92% protein;4.41% fat, and 4.39% crude fiber.